2009
DOI: 10.1111/j.1399-0039.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of an Amerindian contribution to the Polynesian gene pool on Easter Island

Abstract: Available evidence suggests a Polynesian origin of the Easter Island population. We recently found that some native Easter Islanders also carried some common American Indian (Amerindian) human leukocyte antigen (HLA) alleles, which probably were introduced before Europeans discovered the island in 1722. In this study, we report molecular genetic investigations of 21 other selected native Easter Islanders. Analysis of mitochondrial DNA and Y chromosome markers showed no traces of an Amerindian contribution. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 12 publications
4
19
2
1
Order By: Relevance
“…The results have been reported in detail elsewhere [29] and will be only briefly summarized here. (c) Genomic HLA data Because the 21 investigated individuals were unrelated their HLA haplotypes had to be estimated, using methods described in Thorsby et al [29]. Seven of the probable HLA haplotypes found were identical to some found in our previous studies, including haplotype c (see above).…”
Section: Investigations Of New Blood Samples From Easter Islandmentioning
confidence: 99%
“…The results have been reported in detail elsewhere [29] and will be only briefly summarized here. (c) Genomic HLA data Because the 21 investigated individuals were unrelated their HLA haplotypes had to be estimated, using methods described in Thorsby et al [29]. Seven of the probable HLA haplotypes found were identical to some found in our previous studies, including haplotype c (see above).…”
Section: Investigations Of New Blood Samples From Easter Islandmentioning
confidence: 99%
“…Previous genetic studies performed on selected loci (mtDNA, Y chromosome, and HLA complex) [15,16,18] have supported a Polynesian origin of Rapanui. However, a series of archaeological and genetic observations suggest contact between East Polynesians (including Rapanui) and Native Americans prior to the first contact with Europeans.…”
Section: Introductionmentioning
confidence: 97%
“…71-93). Finally, genetic studies of the HLA complex [15][16][17] have identified alleles in Rapanui that are at high frequencies in Native American populations. Lie et al [15] presented evidence that these alleles were introduced prior to the slave raids of the 1860s and concluded that their presence in the population may have predated the first European contact in AD 1722, although data were insufficient to establish this unequivocally (see [17] for review).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vi har i tre studier undersøkt blodprøver fra beboere på Påskeøya som stammer fra den tidlige befolkningen på øya (1)(2)(3). Med DNA-teknologi utførte vi typebestemmelser for mitokondrie-DNA og Y-kromosommarkører samt for alle kjente HLAgenvarianter.…”
unclassified